2013
DOI: 10.1007/s00405-013-2450-z
|View full text |Cite
|
Sign up to set email alerts
|

Is epistaxis associated with arterial hypertension? A systematic review of the literature

Abstract: Both epistaxis and hypertension are frequent problems in the adult population. The relationship between the level of arterial pressure and incidence of epistaxis in a patient with hypertension is a question that appears frequently in the clinical practice. A systematic review of the literature regarding the relation of arterial hypertension with epistaxis was performed through MEDLINE and EMBASE. All studies, whether examining the correlation of arterial pressure at presentation of a patient with nasal bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 22 publications
1
49
2
7
Order By: Relevance
“…Many previous studies have attempted to establish this association, but they have found conflicting results. A recent systematic review was unable to reach a consensus based on the available literature . In our analysis, the association between HTN and epistaxis was significant.…”
Section: Discussioncontrasting
confidence: 60%
“…Many previous studies have attempted to establish this association, but they have found conflicting results. A recent systematic review was unable to reach a consensus based on the available literature . In our analysis, the association between HTN and epistaxis was significant.…”
Section: Discussioncontrasting
confidence: 60%
“…Preexisting arterial hypertension was seen as a confounder and has also been associated with epistaxis in multiple publications [10, 21, 22]. Our number is significantly higher compared to epidemiologic studies which demonstrated a 35–40% prevalence for people above the age of 35 although the steep increase of numbers with age has to be taken into account for our cohort [23].…”
Section: Discussionmentioning
confidence: 80%
“…Most published studies indicate that patients who present with epistaxis have higher blood pressure than controls without epistaxis (37), but it is unclear whether this difference represents actual underlying hypertension (38). Patients with higher blood pressure may also have more severe episodes and require more invasive interventions (39).…”
Section: Discussionmentioning
confidence: 99%